Harmonizing care and identity: Music education, gendered emotional labor, and women’s mental health consciousness - Rong Wang (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
This research explores the intersection of music education and gendered emotional labor in China, focusing on the impact of this intersection on the mental health of women educators. Utilizing theories of emotional labor, gendered care work, and mental health literacy, the study implemented an integrated model through a quantitative cross-sectional survey involving 312 women music educators from urban primary, secondary, and tertiary institutions. Using structural equation modeling, the study revealed that gendered emotional labor significantly contributes to professional identity strain while diminishing mental health awareness. Professional identity strain further dampens mental health consciousness, whereas enhanced mental health awareness predicts improved psychological well-being, resilience, and reduced burnout and anxiety. Mediation analysis demonstrated that the influence of emotional labor on mental health primarily occurs via identity strain and mental health awareness. The study advances emotional labor theory by pinpointing professional identity strain as a critical psychological pathway, reconceptualizes music education as simultaneously nurturing and demanding for women educators, and identifies mental health awareness as a modifiable protective factor. These findings emphasize the importance of culturally attuned, gender-responsive institutional strategies to foster psychological well-being and professional sustainability for women educators in China.